Analysis of current trends in the development of the syndicated loans market in the world and in Ukraine - Borzenko, O.; Kuznietsova, N.V. (Karagandy University of the name of acad. E.A. Buketov, 2022)
Object: The main purpose of the paper is to study the essence and role of syndicated lending in the world economy, to identify changes in this process associated with the Covid-19 pandemic, and also to study the particularities of syndicated lending in Ukraine and to determine the role of Ukrainian companies in this market. The object of the study is the processes of international syndicated lending as one of the most important instruments of financing the activities of major companies and the use of the international experience to enhance the ability of Ukrainian enterprises to attract additional financial resources in the international capital markets. Methods: During the study of syndicated lending development on the global scale and in the Ukrainian market the authors used methods of mathematical analysis and synthesis based on statistical databases published by international analytical agencies and companies, in particular such monthly analytical reviews as Cbonds Review and Cbonds statistical reference books, as well as Thomson Reuters, Loan Market Association databases, etc. The database of the Ministry of Finance of Ukraine was used to study issues related to the development of syndicated lending in Ukraine. Findings: The authors studied this market from the perspective of identification of the structure and functions of the key parties to syndicated lending transactions, analyzed the main banks arranging syndicated lending, the main borrowers and the main areas of investment. The article introduces the main disproportions in the development of the global market of the syndicated lending by regions, member countries, major lending banks and corporate debtors. The article presents the analysis of the participation of Ukraine and Ukrainian borrowers in the processes of international syndicated lending. The analysis of particularities of the development and sectoral orientation of the syndicated loans market in Ukraine for the last 20 years was made; the main imbalances in its development were examined. The main stages and their distinctive features of the development of syndicated lending market in Ukraine were distinguished; the dependence of the intensity of syndicated lending and its sectoral orientation on the changes in the macroeconomic indexes of the country was proved. Conclusions: The article reveals the main disproportions in the development of the world syndicated lending market and its direct dependence on the pace of development of the world economy. The authors defined stages of the development of syndicated lending in Ukraine, their particularities and reasons for the extremely low level of use of this instrument of financing in Ukraine. This paper focuses on the fact that the establishment of an effective system of syndicated lending in Ukraine can help to multiply the potential of the banking system as a whole. Syndicated lending can be used to accumulate the required credit resources, in particular, for large long-term investments in project financing and investment lending.
Әлемдегі жәнеУкраинадағы синдикатталған несиелеу нарығының қaзipri даму тенденцияларын талдау
Анализ текущих тенденций развития рынка синдицированного кредитования в мире и в Украине
Keywords: international financing; syndicated lending; bank loan; Ukrainian syndicated lending market; managing banks (for the syndicated lending); borrowers; financial long-term investments